EKSPLORASI PEMBERDAYAAN MASYARAKAT DALAM PILAR LINGKUNGAN MELALUI PROGRAM PEMBERDAYAAN KELUARGA - Arif Abdul Haqq; Zakiyyah Zakiyyah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2019)
As with environmental problems in general, Kubangwungu Village also has issues in the ecological field, namely some people who still have the habit of littering. So that rubbish littered clogged waterways and piled up in rivers. This causes the river to overflow and flood. This research aims to give a comprehensive picture of the implementation of community empowerment in the pillars of the environment through the family empowerment program (POSDAYA). This type of research is descriptive research with a partnership program. The results showed that the implementation of family-based community empowerment activities was carried out from July 2019 to August 2019 in Kubangwungu Village, Ketanggungan District, Brebes Regency, Central Java Province. Optimizing the role of the family as an activity center is a significant factor in the implementation of family-based posdaya activities. These activities include making nutritious gardens, utilizing household waste, making biopori, making waste banks, management, and mechanisms of waste banks. These activities turned out to be able to increase public awareness of the environment as an implication of community empowerment in the environmental field